Trends in school mental health and substance use education - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott E.; Benes, Sarah S. (JAMA, 2025)
The percentage of US youths experiencing mental health and substance use problems has risen rapidly in recent years. Schools are important settings for prevention, but whether preventive programming meets student needs is unknown. This study examined trends in school programming related to mental health and substance use and teacher professional development across US middle and high schools from 2008-2020.
Keywords: dept.hms; peer-reviewed